Protective effects of caffeic acid phenethyl ester (CAPE) on carbon tetrachloride-induced hepatotoxicity in rats - Kus, L; Colakoglu, N; Pekmez, H; Seckin, D; Ogeturk, M; Sarsilmaz, M (Elsevier Gmbh, 2004)
In the present study, protective effects of caffeic acid phenethyl ester (CAPE) have been evaluated on carbon tetrachloride (CCl4)-induced hepatotoxicity in rat. Twenty-four mate Wistar rats were divided in three groups. Group I was used as control. Rats in group II were injected every other day with CCl4 for 1 month, whereas rats in group III were injected every other day with CCl4 and CAPE for 1 month. At the end of the experiment, all animals were killed by decapitation and blood samples were obtained. Serum aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, total and conjugated bilirubin levels and hepatic malondialdehyde (MDA) contents were determined. For histopathological. evaluation, Livers of all rats were removed and processed for light microscopy. All biochemical parameters in serum and the hepatic MDA content were significantly higher in animals treated with CCl4 than in the controls. Rats treated with CCl4 and CAPE showed a significant reduction in biochemical parameters in serum and hepatic MDA content. Livers of rats treated with CCl4 showed classic histology of cirrhosis, whereas the histopathological changes were reduced after administration Of CCl4 and CAPE. A normal. lobular appearance was observed in Livers in this group except for fatty degeneration. The results of our study indicate that CAPE treatment prevents CCl4-induced liver damage in rats. (C) 2004 Elsevier GmbH. All rights reserved.
Keywords: caffeic acid phenethyl ester (CAPE); carbon tetrachloride; hepatotoxicity; light microscopy; rat